PENGARUH SIFAT KEPRIBADIAN TERHADAP INTENSI MENJADI WIRAUSAHA DENGAN EFIKASI DIRI SEBAGAI VARIABEL INTERVENING (STUDI PADA MAHASISWA FAKULTAS EKONOMIKA DAN BISNIS UNIVERSITAS DIPONEGORO SEMARANG) - Mesach Hendri Dwi Larviatmo; Intan Ratnawati (Faculty of Economics and Business Diponegoro University, 2018)
This study aims to analyze the effect of personality traits on entrepreneurial intention with self efficacy as mediators. This study uses Big Five Personality Traits as independent variables, entrepreneurial intention as the dependent variable, and self efficacy as intervening variables.This study took a study on students of the Faculty of Economics and Business, Diponegoro University, Semarang. The sample in this study amounted to 150 respondents who were all students of the 2014 Faculty of Economics and Business Faculty of Diponegoro University and had taken the eighth semester.In this study using a Structural Equation Modeling (SEM) analysis tool by developing a theoretical model using three hypotheses that operate using the AMOS 20.0 computing program. Based on the results of data processing using SEM, the theoretical model established has met the criteria for goodness of fit is accepted. Based on the results obtained, the model is declared feasible to use. The results of testing hypotheses show that all hypotheses have a positive effect. The results of mediation testing also showed a significant influence that self-efficacy had a positive effect as a mediator for personality traits and entrepreneurial intention.